Revista Peruana de Ginecologia y Obstetricia. Last 15 years - Pacheco Romero, José (2015)
Introduction: Revista Peruana de Ginecologia y Obstetricia current Editorial Committee has been in charge of the Sociedad Peruana de Obstetricia y Ginecologia official journal during the last 15 years, time of extraordinary advances in the specialty. Objectives: To determine types and characteristics of scientific papers published in the Revista Peruana de Ginecologia y Obstetricia in the last 15 years and if they keep relation with research in the specialty. Design: Documental, descriptive research. Journal: Revista Peruana de Ginecologia y Obstetricia, indexed biomedical journal. Material: Revista Peruana de Ginecologia y Obstetricia publications from 1994 through 2008. Interventions: From 1994 through 2008 Revista Peruana de Ginecologia y Obstetricia publication and author indexes are reviewed, determining types and characteristics of publication, reasons of content modifications, authors with more publications, indexation. Main outcome measures: Publications types and characteristics and authors that published more. Results: Since 1994, 592 original specialty papers and 53 Editorials have been published, totaling 645 articles. There has been an average of 5,6 original papers per number or 50,5% of the whole production. The 46 review papers signified an average of 0,8 per number and 7,1% of the production. We published twelve symposia, totaling 74 topics and an average of 6,2 symposium subthemes per number. We found 551 single or first authors and 887 coauthors. Conclusions: Revista Peruana de Ginecologia y Obstetricia has maintained permanence, periodicity and punctuality and has improved its quality as a scientific publication during these 15 years influenced by advances in the specialty of Obstetrics and Gynecology and by Vancouver norms and data bases requisites.